Gadget as Risk Factor to Speech and Language Delay in Autism Children (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
Users gadgets not only among adults but the age of adolescence and early age as a kindergartner and a toddler was already using the gadget. The child’s brain at the age of 0-5 years is in the golden development period (golden age). Toddler is the most important period in optimally increasing children’s development because it can influ-ence and determine children’s development going forward. The use of gadgets from an early age will have an im-pact on children’s development that can trigger the incidence of autism. The purposed of this studied was to de-termine the effect of using gadgets on developmental delays in speech and language aspects in children with au-tism. This type of research is an observational analytic studied used a cross sectional approach. Respondents numbered 33 people. This research was conducted at the Autonomous Service UPTD of Southeast Sulawesi Edu-cation Office. Bivariate analysis showed that the intensity of the use of gadgets was related to the development of speech and language (p value = 0.011; OR = 16,000). In this case, parental supervision is very important in providing limits and controlling the playing time of the gadget to optimize the growth and development of children.